Asymptotic behavior analysis of complex-valued impulsive differential systems with time-varying delays. (February 2018) - Xu, Liguang; Ge, Shuzhi Sam
Abstract: In this paper, asymptotic behavior analysis is addressed for a class of nonlinear complex-valued impulsive differential systems with time-varying delays. By establishing two inhomogeneous impulsive delay differential inequalities and applying the theory of matrix measure, the global exponentially attractive set, invariant set and weak-invariant set of the complex-valued impulsive delay differential systems are derived. Examples are provided to illustrate the effectiveness of the proposed results.